Big to Small: Ultrafine Mo2C Particles Derived from Giant Polyoxomolybdate Clusters for Hydrogen Evolution Reaction. Issue 11 (8th February 2019) - Zhou, Zheng; Yuan, Ziwen; Li, Sai; Li, Hao; Chen, Junsheng; Wang, Yanqing; Huang, Qianwei; Wang, Cheng; Karahan, Huseyin Enis; Henkelman, Graeme; Liao, Xiaozhou; Wei, Li; et al.
Abstract: Due to its electronic structure, similar to platinum, molybdenum carbides (Mo2 C) hold great promise as a cost‐effective catalyst platform. However, the realization of high‐performance Mo2 C catalysts is still limited because controlling their particle size and catalytic activity is challenging with current synthesis methods. Here, the synthesis of ultrafine β‐Mo2 C nanoparticles with narrow size distribution (2.5 ± 0.7 nm) and high mass loading (up to 27.5 wt%) on graphene substrate using a giant Mo‐based polyoxomolybdate cluster, Mo132 ((NH4 )42 [Mo132 O372 (CH3 COO)30 (H2 O)72 ]·10CH3 COONH4 ·300H2 O) is demonstrated. Moreover, a nitrogen‐containing polymeric binder (polyethyleneimine) is used to create MoN bonds between Mo2 C nanoparticles and nitrogen‐doped graphene layers, which significantly enhance the catalytic activity of Mo2 C for the hydrogen evolution reaction, as is revealed by X‐ray photoelectron spectroscopy and density functional theory calculations. The optimal Mo2 C catalyst shows a large exchange current density of 1.19 mA cm −2, a high turnover frequency of 0.70 s −1 as well as excellent durability. The demonstrated new strategy opens up the possibility of developing practical platinum substitutes based on Mo2 C for various catalytic applications. Abstract : Giant molybdenum‐based polyoxometalate clusters create ultrafine molybdenum carbide nanoparticles with smaller and narrower size distribution and superior catalytic activity for the hydrogen evolution reaction.